ANALISIS ASUHAN KEPERAWATAN DENGANINTERVENSI TERAPI KOMPLEMENTER SWEDISHMASSAGE TERHADAP PENURUNAN TEKANAN DARAHPADA PASIEN HIPERTENSI GRADE II DI RUANGFLAMBOYAN RS BHAYANGKARA TK. I RADEN SAIDSUKANTO - Regita Cahyani Zarlis (2022)
Hypertension is a state of increasing systolic blood above the normal value of more than 140 mmHg and diastolic pressure of more than 90 mmHg (WHO, 2018). Signs and symptoms experienced by people with hypertension include blood pressure above normal, namely systolic pressure above 140 mmHg, and diastolic pressure above 80 mmHg, impaired vision, blurry and unclear, headache, feeling nauseated and vomiting, feeling weak, and restless (Smeltzer & Bare, 2017). Hypertension cannot be taken easyly. There are many ways to treat and prevent hypertension, both pharmacologically, namely taking drugs and nonpharmacological such as SEFT therapy, progressive muscle relaxation, deep breathing relaxation techniques, reflexology that can lower blood pressure (Kusuma et al., 2021). One of the interventions that I will use in this nursing care is Swedish Massage therapy, namely manipulation of body tissues by doing massage using five basic movements, including effleurage, petrisage, friction, tapotement and vibration (Beck, 2012). The purpose of this study was to determine whether there was a change in blood pressure in Hypertension Grade II patients before and after Swedish massage therapy was given to managed and resumed patients.